Analisis Manajemen Acara Pasca-pandemi: Studi Kasus Pesta Rakyat Dewa-19 2023 Bandung - Aryowibowo, Seno Adji; Prasetio, Arie (eProceedings of Management, 2024)
One form of event that has the most interest in Indonesia is music concert events. The Covid-19 pandemic has broughtall kinds of activities in the field of events to a halt for connoisseurs, organizers, and stakeholders involved in the fieldof events. As a result of the pandemic, various companies in the field of events have come to a standstill and even wentbankrupt because they could not organize events. However, after the pandemic ended, one of the first concerts heldin Bandung was the Dewa-19 People's Party Concert. This research aims to find out the stages of MCM LiveProduction's event management in organizing the Pesta Rakyat Dewa-19 event. This research refers to the theory ofEvent Management Stages by Joe Goldblatt with 5 stages namely Research, Design, Planning, Coordination andEvaluation. The research method used is Qualitative Method with the approach of Case Study. The case study used isthe Pesta Rakyat dewa-19 Bandung Year 2023 organized by MCM Live Production. The stages of event managementwere obtained at the MCM Live Production Event Organizer in carrying out the 2023 Bandung God-19 People's Partyevent. The stages carried out are in line with what is stated by Goldblatt but with slight differences. Keywords-event management, Covid-19 pandemics, MCM Live Production, Dewa-19.